THE IMPORTANCE OF ENGLISH TEACHING METHODS IN JURIDICAL EDUCATION - Xudoyorova, Nafisa Baxtiyor qizi; Nuritdinova, Ferangiz Murodullayevna (INTERNATIONAL CONFERENCES, 2022)
This article is about the significance of English teaching methods, approaches and techniques for law students.